2019
DOI: 10.1017/s0022215119000574
|View full text |Cite
|
Sign up to set email alerts
|

Palliative intent treatment for head and neck cancer: an analysis of practice and outcomes

Abstract: BackgroundThere is little consensus on how best to manage head and neck cancer with palliative intent. Predicting outcome is difficult and reported survival varies. The present study sought to delineate local practice and outcomes in patients treated with palliative intent.MethodsThe clinical records of all head and neck cancer patients treated with palliative intent presenting between 2015 and 2016 to our multidisciplinary team were reviewed.ResultsEighty-four patients (21.5 per cent) were treated with pallia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Our results were similar with these results. Considering that the prognosis of patients with HNC who undergo noncurative treatment is poor with approximate survival time of 2-4 months [25,26], palliative RT may contribute to a certin degree of prolonged survival. However, more than half of the patients die within 6 months even if they undergo palliative RT, including RTOG 8502 regimen [4,5,7,8,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Our results were similar with these results. Considering that the prognosis of patients with HNC who undergo noncurative treatment is poor with approximate survival time of 2-4 months [25,26], palliative RT may contribute to a certin degree of prolonged survival. However, more than half of the patients die within 6 months even if they undergo palliative RT, including RTOG 8502 regimen [4,5,7,8,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…47,48 In one study, 84/390 (21.5%) people with head and neck cancer were treated with palliative intent following diagnosis. 49 Third, the extent of missing data, especially for the place and mode of death, and the fact that data were recorded by the research team (rather than the clinical team) may limit their accuracy. More robust methods of eliciting this information would be useful within future research.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%
“…This is in keeping with previous work in our region pre-COVID-19 which demonstrated that 21% of cases were unsuitable for active anti-cancer treatment, reflecting the significant co-morbidities, poor PS and advanced disease stage we frequently encounter in our cancer network and confirming that patients are not being denied anti-cancer treatment as a result of COVID-19. [40] To date, epidemiological studies have included patients with several different types of cancer and confirmed COVID-19 infection; patients with HNC have made up only a small proportion of these cases. In addition, it is difficult to put the potential risks of COVID-19 infection as a result of HNC treatment into perspective without knowledge of the outcomes of all patients treated during the pandemic.…”
Section: Discussionmentioning
confidence: 99%